Real-world evidence of tisagenlecleucel for pediatric acute lymphoblastic leukemia and non-Hodgkin lymphoma - Pasquini, Marcelo C. (Blood Adv, 2020)
Tisagenlecleucel is a CD19 chimeric antigen receptor (CAR) T-cell therapy approved for treatment of pediatric and young adult patients with relapsed/refractory acute lymphoblastic leukemia (ALL) and adults with non-Hodgkin lymphoma (NHL). The initial experience with tisagenlecleucel in a real-world setting from a cellular therapy registry is presented here. As of January 2020, 511 patients were enrolled from 73 centers, and 410 patients had follow-up data reported (ALL, n = 255; NHL, n = 155), with a median follow-up of 13.4 and 11.9 months for ALL and NHL, respectively. Among patients with ALL, the initial complete remission (CR) rate was 85.5%. Twelve-month duration of response (DOR), event-free survival, and overall survival (OS) rates were 60.9%, 52.4%, and 77.2%, respectively. Among adults with NHL, the best overall response rate was 61.8%, including an initial CR rate of 39.5%. Six-month DOR, progression-free survival, and OS rates were 55.3%, 38.7%, and 70.7%, respectively. Grade ≥3 cytokine release syndrome and neurotoxicity were reported in 11.6% and 7.5% of all patients, respectively. Similar outcomes were observed in patients with in-specification and out-of-specification products as a result of viability <80% (range, 61% to 79%). This first report of tisagenlecleucel in the real-world setting demonstrates outcomes with similar efficacy and improved safety compared with those seen in the pivotal trials.